Artificial Fertilization Techniques in Bronze Featherback (Notopterus notopterus): First Report and Preliminary Findings - Asep Permana; Agus Priyadi; Lukman; Bastiar Nur; Sulasy Rohmy; Sawung Cindelaras; Rendy Ginanjar; Ainulyakin Imlani; Darmawan Setia Budi (Airlangga University, 2025)
The Java-native bronze featherback (Belida Jawa), Notopterus notopterus, has been designated as a protected species under limited protection status by the Decree of the Minister of Maritime Affairs and Fisheries of Indonesia No. 83 of 2024, with captive breeding efforts undertaken for conservation and aquaculture to meet increasing consumer demand. This study provides a preliminary evaluation of artificial fertilization techniques in N. notopterus, focusing on hormone-induced spawning using Ovaprim™. The objective was to determine the effectiveness of hormone injection, optimal egg stripping timing, and hatching success under controlled water quality conditions. Two female broodstock received different dosages of Ovaprim™, and successful egg stripping was conducted after a 41-hour latency period. Fertilization rates of 30% and 11.23% were observed for the first and second females, respectively; however, hatching success remained extremely low at 0.52% for the first female, with no larvae hatching from the second. Despite maintaining water quality parameters such as temperature, pH, conductivity, and total dissolved solids within acceptable limits, the poor hatching rate suggests that additional factors, including ammonia concentration and dissolved oxygen levels, may have impacted embryonic development. This study establishes a foundational basis for artificial reproduction in N. notopterus, emphasizing the need for further research to optimize hormone protocols, sperm viability, and environmental conditions. These findings contribute to the advancement of aquaculture strategies for the conservation and sustainable management of this ecologically important species.